RISK ANALYSIS OF THE NEWSVENDOR PROBLEM BASED ON STEADY RISK PREFERENCE - Zhu, Mingjun (Advances in Social Sciences Research Journal, 2018)
A new risk measurement method was used in this paper to analyze the risk of newsvendor problem. Through the study we found for the action of same order quantity decision, risk values of the action are different for decision makers who have different risk preference. For the same order quantity risk value of high profit product is always lower the low profit product. With increase of order quantity the increment of risk valuewill first decrease and then increase.